Pallister-Hall syndrome and McKusick-Kaufmann syndrome: one entity?. Issue 2 (February 1995) - Unsinn, K M; Neu, N; Krejci, A; Posch, A; Menardi, G; Gassner, I
Abstract : The Pallister-Hall syndrome is characterised by specific facial anomalies, postaxial polydactyly, imperforate anus, and brain anomalies including a diencephalic hamartoblastoma. The hallmarks of the McKusick-Kaufmann syndrome are hydrocolpos owing to vaginal atresia, postaxial polydactyly, imperforate anus, and congenital heart defects. We report a patient with the unique features of hydrocolpos, postaxial polydactyly, and hypothalamic hamartoblastoma and discuss the different aetiological considerations of both syndromes and implications for clinical management.